Evaluation of Therapeutic Efficacy and Imaging Capabilities of 153Sm2O3-Loaded Polystyrene Microspheres for Intra-Tumoural Radionuclide Therapy of Liver Cancer Using Sprague-Dawley Rat Model - Hun Yee Tan; Yin How Wong; Azahari Kasbollah; Mohammad Nazri Md Shah; Noorazrul Yahya; Basri Johan Jeet Abdullah; Chai Hong Yeong (MDPI AG, 2023)
Introduction: Neutron-activated samarium-153-oxide-loaded polystyrene ([153Sm]Sm2O3-PS) microspheres has been developed in previous study as a potential theranostic agent for hepatic radioembolization. In this study, the therapeutic efficacy and diagnostic imaging capabilities of the formulation was assessed using liver cancer Sprague-Dawley (SD) rat model. Methods: Twelve male SD rats (150-200 g) that implanted with N1-S1 hepatoma cell line orthotopically were divided into two groups (study versus control) to monitor the tumour growth along 60 days of treatment. The study group received an intra-tumoural injection of approximately 37 MBq of [153Sm]Sm2O3-PS microspheres, while control group received an intra-tumoural injection of 0.1 mL of saline solution. A clinical single photon emission computed tomography/computed tomography (SPECT/CT) system was used to scan the rats at Day 5 post-injection to investigate the diagnostic imaging capabilities of the microspheres. All rats were monitored for change in tumour volume using a portable ultrasound system throughout the study period. Histopathological examination (HPE) was performed after the rats were euthanized at Day 60. Results: At Day 60, no tumour was observed on the ultrasound images of all rats in the study group. In contrast, the tumour volumes in the control group were 24-fold larger compared to baseline. Statistically significant difference was observed in tumour volumes between the study and control groups (p < 0.05). The SPECT/CT images clearly displayed the location of [153Sm]Sm2O3-PS in the liver tumour of all rats at Day 5 post-injection. Additionally, the [153Sm]Sm2O3-PS microspheres was visible on the CT images and this has added to the benefits of 153Sm as a CT contrast agent. The HPE results showed that the [153Sm]Sm2O3-PS microspheres remained concentrated at the injection site with no tumour cells observed in the study group. Conclusions: Neutron-activated [153Sm]Sm2O3-PS microspheres demonstrated excellent therapeutic and diagnostic imaging capabilities for theranostic treatment of liver cancer in a SD rat model. Further studies with different animal and tumour models are planned to validate this finding.